Antitumor Efficacy of Human Monocyte-Derived Dendritic Cells - Marques, Graça S. (2018)
Background: Dendritic cells (DCs), which can be used as anti-cancer vaccines, are generally obtained in vitro from isolated CD14+ monocytes (MoDCs). This generates high cell numbers and allows instructing DCs to guarantee effective antitumor responses. However, the impact of the monocyte isolation step in the antitumor effectiveness of the generated MoDCs is still unknown. Here, we compared the most used immunomagnetic technologies for monocyte isolation: magnetic activated cell sorting (MACS) from Miltenyi Biotec and EasySep from STEM CELL. Results: MACS technology allowed a higher monocyte yield and purity and, by flow cytometry, monocytes displayed higher size and lower granularity. In the resting state, EasySep-MoDCs showed a higher basal expression of HLA-DR, and no significant response to stimulation by LPS and TNF-α. When stimulated with whole tumor cells lysates, both MoDCs expressed similar levels of maturation and co-stimulatory markers. However, when cultured with autologous T cells, MACS-MoDCs induced significantly higher IFN-γ secretion than EasySep-MoDCs, indicating a stronger induction of Th1 cell response profile. Concordantly, T cells induced by MACS-MoDCs also showed a higher release of cytotoxic granules when in contact with tumor cells. Conclusions: Overall, both the MACS and the EasySep isolation immunomagnetic technologies provide monocytes that differentiate into viable and functional MoDCs. In our experimental settings, resting EasySep-MoDCs showed a higher basal level of maturation but show less responsivity to stimuli. On the other hand, MACS-MoDCs, when stimulated with tumor antigens, showed better ability to stimulate Th1 responses and to induce T cell cytotoxicity against tumor cells. Thus, monocyte isolation techniques crucially affect MoDCs' function and, therefore, should be carefully selected to obtain the desired functionality.